2014
DOI: 10.1007/978-3-319-13177-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Efficiency of Humanitarian Supply Chains: Evidence from French Red Cross Operations

Abstract: Natural catastrophes are often amplified by man-made impact on the environment. Sustainability is identified as a major gap in humanitarian logistics research literature. Although humanitarian supply chains are designed for speed and sustainability is of minor concern, environmentally-friendly behavior (e.g. through reduction of transportation emissions and avoidance of non-degradable materials) should be a long-term concern as it may ultimately affect more vulnerable regions. The purpose of this paper is to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Research on sustainable humanitarian supply chains is often qualitative [35][36][37][38]. Therefore, a limited number of studies proposed quantitative approaches and developed mathematical models [5,[39][40][41][42][43][44][45][46][47]. However, the most relevant studies do not sufficiently consider all aspects of sustainability under disruptions in relief operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on sustainable humanitarian supply chains is often qualitative [35][36][37][38]. Therefore, a limited number of studies proposed quantitative approaches and developed mathematical models [5,[39][40][41][42][43][44][45][46][47]. However, the most relevant studies do not sufficiently consider all aspects of sustainability under disruptions in relief operations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This model is based on a sophisticated network simulation whose data are from the whole country and can calculate any amount of energy usage and carbon emissions. Oberhofer et al (2014) studied the carbon performance of a humanitarian supply chain, focusing on the French Red Cross Society, and calculated the carbon footprint of supply chain products from manufacturing to disposal. Zhang and Chen (2019) used the garment‐manufacturing sector as the study object to develop the carbon emission evaluation model, and findings revealed that fabrics and accessories are the primary sources of carbon emissions in garment sewing production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, for aftermath reconstruction projects, advanced construction technology is a solid enabler of adding a value to the economy, society and environment and to get the desired results in HSC operations (Amadei et al , 2009). Also, choice of degradable materials is also to be considered for greening the HSCs (Oberhofer et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%